Weekly Versus Daily Levothyroxine Tablet Replacement in Adults with Hypothyroidism: A Meta-Analysis - Chiu, Harold Henrison; Larrazabal, Ramon; Uy, Angelique Bea; Jimeno, Cecilia (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Objectives. Daily levothyroxine is the treatment of choice and standard of care in hypothyroidism, sufficient to restore thyroid stimulating hormone (TSH) to normal range. For many patients, daily lifelong therapy is required, making adherence a major issue. In such cases, weekly replacement may be a suitable alternative to improve adherence. In this study, we aimed to determine the efficacy and safety of weekly levothyroxine replacement among adults with hypothyroidism. Methodology. Electronic databases were searched. Two reviewers (HCC and RBL) independently screened the abstracts, reviewed full-text papers, critically appraised the quality of included studies using PRISMA guidelines. Meta-analysis was performed using the random-effects model. The primary outcome is the difference in serum TSH levels between weekly and daily administration, while secondary outcomes included adverse events and symptoms of hypothyroidism. Results. The primary outcome is the difference in serum TSH levels between weekly and daily administration. Secondary outcomes included adverse events and clinical symptoms. The study included two randomized trials (n=109) in the primary analysis. The difference in TSH levels was 1.78 mIU/mL higher [(95% confidence interval (CI): 1.28 to 2.28, p<0.00001] at 6 weeks and 1.22 mIU/mL higher (95% CI: 0.76 to 1.67, p<0.00001) at 12 weeks for the weekly regimen. There was no significant heterogeneity between the two groups. There was no significant difference in hypothyroid symptoms and adverse events before and after levothyroxine treatment within each group. Conclusions. Weekly levothyroxine resulted in less suppression and higher mean serum TSH levels, while still remaining within the normal reference range. It may be a suitable alternative for non-adherent patients. However, larger randomized trials with longer duration of follow-up are needed to firmly establish its role.